2009
DOI: 10.1007/s00467-008-1072-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and developmental basis for urinary tract obstruction

Abstract: Urinary tract obstruction results in obstructive nephropathy and uropathy. It is the most frequent cause of renal failure in infants and children. In the past two decades, studies in transgenic models and humans have greatly enhanced our understanding of the genetic factors and developmental processes important in urinary tract obstruction. The emerging picture is that development of the urinary tract requires precise integration of a variety of progenitor cell populations of different embryonic origins. Such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 94 publications
1
40
0
2
Order By: Relevance
“…mimic the human CAKUT that are the most common cause of renal failure in children (33,34). In addition, we also observed renal dysplasia, cystic disease, hydronephrosis, hydroureter, and collecting system duplication in Lzts2 null embryos, neonates, and adult mice.…”
Section: Discussionsupporting
confidence: 61%
“…mimic the human CAKUT that are the most common cause of renal failure in children (33,34). In addition, we also observed renal dysplasia, cystic disease, hydronephrosis, hydroureter, and collecting system duplication in Lzts2 null embryos, neonates, and adult mice.…”
Section: Discussionsupporting
confidence: 61%
“…We thus suspect that functional defects in handling urine transport or polyuria may be the primary cause of hydronephrosis, although other causes cannot be excluded at this point. [17][18][19] Absence of Adam10 in Collecting Duct Progenitor Cells Results in an Altered Ratio of PCs to ICs To distinguish the two main cell types in the collecting duct, namely the PCs and the ICs, we performed immunofluorescence staining on kidney sections with Aqp2 (a PC marker), and ATPase (an IC marker) (Figure 2, A-H). The proportion of ATPase + ICs was significantly higher in the mutants than in the controls (Figure 2, A-F and I).…”
Section: Deletion Of Adam10 In Ub Derivatives Led To Polyuria and Hydmentioning
confidence: 99%
“…Polyuria has the potential to eventually overwhelm the pyeloureteral peristaltic machinery for urine transfer, leading to hydronephrosis and renal failure. [17][18][19] Because the mice with hydronephrosis had various degrees of erosion of the renal parenchyma starting from the inner medulla, we analyzed these mice separately and focused mostly on the cortex, where structures were still relatively intact and recognizable. We found that the percentage of ATPase + ICs in the cortex was similar between mutants with hydronephrosis (46.51% 64.38%) and mutants without hydronephrosis (46.91% 65.49%) (P=0.68).…”
Section: Deletion Of Adam10 In Ub Derivatives Led To Polyuria and Hydmentioning
confidence: 99%
“…22 Continuing advances in mouse genetics and genomics will no doubt speed up the identification of the genetic factors and pathways involved in the pathogenesis of obstructive nephropathy.…”
Section: Calcineurin Is Required For the Development Of The Pyelouretmentioning
confidence: 99%